2013
DOI: 10.1210/jc.2013-2292
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next-Generation Sequencing Panel (ThyroSeq) for Detection of Mutations in Thyroid Cancer

Abstract: The ThyroSeq NGS panel allows simultaneous testing for multiple mutations with high accuracy and sensitivity, requires a small amount of DNA and can be performed in a variety of thyroid tissue and fine-needle aspiration samples, and provides quantitative assessment of mutant alleles. Using this approach, the point mutations were detected in 30%-83% of specific types of thyroid cancer and in only 6% of benign thyroid nodules and were shown to be present in the majority of cells within the cancer nodule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
364
2
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 428 publications
(389 citation statements)
references
References 56 publications
16
364
2
7
Order By: Relevance
“…However, these pyrosequencing data are in contrast to the results achieved using NGS and IHC staining. Nikiforova et al (2013) evaluated BRAF mutated alleles using NGS and reported that 80% of PTCs with BRAF V600E had more than 25% of the mutated alleles. In the TCGA dataset, 86% of classic PTCs with BRAF V600E had more than 25% of the mutated alleles.…”
Section: Discussionmentioning
confidence: 99%
“…However, these pyrosequencing data are in contrast to the results achieved using NGS and IHC staining. Nikiforova et al (2013) evaluated BRAF mutated alleles using NGS and reported that 80% of PTCs with BRAF V600E had more than 25% of the mutated alleles. In the TCGA dataset, 86% of classic PTCs with BRAF V600E had more than 25% of the mutated alleles.…”
Section: Discussionmentioning
confidence: 99%
“…36 The performance of this genetic panel was initially evaluated by using thyroid tumors cells and cell lines with known genetic alterations. The ThyroSeq test had a 100% analytic accuracy, as it correctly detected all pathogenic mutations in previously positive thyroid tumor samples and cell lines.…”
Section: Afirma Gene Expression Classifiermentioning
confidence: 99%
“…In addition, all mutations detected by ThyroSeq were confirmed by other molecular testing methods, such as Sanger sequencing, real-time PCR, or coamplification at lower denaturation-PCR, revealing 100% correlation among the different techniques. The initial validation of ThyroSeq panel by Nikiforova et al 36 showed the presence of the tested gene mutations or translocations in various thyroid malignancies, including 19 of 27 classic PTCs (70%), 25 of 30 follicular variant PTCs (83%), 14 of 18 conventional carcinomas (78%), 7 of 18 oncocytic follicular carcinomas (39%), 3 of 10 poorly differentiated carcinomas (30%), 20 of 27 anaplastic thyroid carcinomas (ATCs) (74%), and 11 of 15 medullary thyroid carcinomas (73%). In contrast, only 5 of 83 benign nodules (6%) were positive for mutations.…”
Section: Afirma Gene Expression Classifiermentioning
confidence: 99%
“…Sporadic medullary thyroid carcinomas with wild-type RET genes may harbor RAS mutations (HRAS or KRAS). 2,4,5,8,15,16 D. PIK3CA, AKT1, and TP53 Mutational Analysis PIK3CA, AKT1, and TP53 mutations are usually found in advanced thyroid cancer with propensity for dedifferentiation and distant metastasis. 8,17 E. CTNNB1 Mutational Analysis…”
Section: Ras Mutational Analysismentioning
confidence: 99%